Pengembangan Sistem Ticketing Berbasis Web Menggunakan Metode Waterfall untuk Manajemen Layanan TI - Salwa Az-Zahra Munir; Nugroho Dwi Saputra (TIN: Terapan Informatika Nusantara, 2026)
Systematic service management is crucial for internet service providers. PT Ikhlas Cipta Teknologi faces the problem of decentralized management of customer complaints and service requests due to its reliance solely on the WhatsApp instant messaging app. This practice often leads to missed reports, loss of problem resolution records, and unmeasurable technician handling times. The objective of this research is to design and build a web-based internal Ticketing Information System tailored to the company's operational needs to address these issues. The system was developed using the Waterfall method, utilizing the Next.js framework, and the MongoDB Atlas database. The proposed solution includes digitizing complaints into structured tickets, a deadline monitoring mechanism through a Service Level Agreement (SLA), and a four-level escalation flow: Customer Service, Helpdesk, Network Operation Center (NOC), and Super NOC. Black Box Testing evaluation results demonstrated that all system functionality ran smoothly. Furthermore, the results of the feasibility test from end users through User Acceptance Testing (UAT) recorded a percentage of 93.6%. This figure indicates a very good level of system acceptance. The implementation of this system is able to improve the management of complaints or customer service requests by converting reports into structured data, providing a more transparent handling history, and monitoring resolution times accurately, thereby supporting the improvement of the company's operational effectiveness. The research contributes by integrating Service Level Agreements (SLAs), Role-Based Access Control (RBAC), and a four-tier escalation mechanism into a web-based internal ticketing system, facilitating more structured incident management within an ISP environment.